Efektivitas Latihan Low Impact dan High Impact terhadap Penurunan Kadar Kolesterol Total pada Penderita Hipertensi - Najla Iffathiya; Ummy A'isyah Nurhayati; Rizky fis Wulandari (Borneo Nursing Journal (BNJ), 2026)
Hypertension is a major cardiovascular risk factor often associated withhypercholesterolemia. Aerobic exercise is recommended as a non-pharmacological intervention toimprove lipid profiles. Objective: To determine and compare the effectiveness of low-impact and high-impact exercise in reducing total cholesterol levels among patients with hypertension. Methods: Aquasi-experimental study with a pretest–posttest two-group design was conducted on 28 hypertensivepatients aged 50–70 years at Mlati 2 Community Health Center. Participants were assigned to a low-impact group (n = 14; brisk walking) and a high-impact group (n = 14; High-Intensity IntervalTraining [HIIT] running in place) for four weeks, three sessions per week. Data were analyzed usingthe Paired Sample t-test and Mann–Whitney test (α = 0.05). Results: The low-impact group showed anon-significant reduction in total cholesterol levels from 213.93 ± 8.66 mg/dL to 210.93 ± 13.88mg/dL (p = 0.503). In contrast, the high-impact group demonstrated a significant reduction from224.93 ± 20.13 mg/dL to 201.86 ± 22.66 mg/dL (p = 0.011). However, no significant difference ineffectiveness was found between the two exercise modalities (p = 0.077). Conclusion: High-impactexercise effectively reduced total cholesterol levels, while low-impact exercise showed only a slightreduction. Nevertheless, both interventions demonstrated comparable effectiveness statistically.